Spatiotemporal factors affecting a single hurdle clearance technique: is "faster" the same as "increased technique efficiency"? - Ozaki, Y.; Ueda, T. (International Journal of Performance Analysis in Sport, 2022)
This study aimed to identify the spatiotemporal characteristics in technical hurdle clearance considering differences in centre of mass (CM) height and sprint ability. Spatiotemporal variables were calculated for 13 male hurdlers by capturing hurdle clearances at the same height as their respective CM and hurdle-free sprints with a high-speed camera. Relationships between each variable and the horizontal velocity during hurdle clearance (HC-v), ratio of HC-v to sprint velocity without hurdles (HC-index), rate of deceleration on takeoff (D-takeoff), and rate of deceleration on landing (D-landing) were examined. Results showed that the support time on takeoff was not significantly correlated with the HC-index, and the correlation coefficient with the release height of CM at landing was significantly higher for the HC-index than for the HC-v. After stepwise multiple regression analysis, the following explanatory variables were selected as promising: clearance time for HC-v, long release distance on takeoff and high release height of CM at landing for HC-index, short touchdown distance on takeoff and long release distance on takeoff for D-takeoff, and takeoff-landing distance ratio for D-landing. These results suggest that the spatiotemporal variables that are important for speed, technicality, and low deceleration on takeoff versus on landing during hurdle clearance are different.